Randomized trial of different initial intravenous immunoglobulin regimens in Kawasaki disease. Issue 7 (16th June 2021) - He, Lan; Liu, Fang; Yan, Weili; Huang, Min; Huang, Meirong; Xie, Lijian; Guo, Ying; Xu, Xinyi; Chu, Chen; Wu, Lin; Liang, Xuecun; Sun, Shuna; et al.
Abstract: Background: We aimed to assess the efficacy of different initial intravenous immunoglobulin (IVIG) regimens in Kawasaki disease (KD) patients to find more cost‐effective therapy options. Methods: A multicenter, open‐label, blind‐endpoint randomized controlled trial was conducted from January 2014 to December 2015. Patients with KD, within 10 days of illness, were randomly assigned to receive different IVIG regimens (Group A, 2 g/kg once; Group B, 1 g/kg for 2 consecutive days; Group C, 1 g/kg once) and aspirin 30mg/kg/d. Primary outcomes included hours to defervescence and development of coronary artery lesions during the study period. Major secondary outcomes included total fever days, total dose of IVIG, changes of laboratory data, length of stay, and hospitalization expenses. (ClinicalTrials.gov: NCT02439996). Results: A total of 404 patients underwent randomization. No difference was found in the outcomes of defervescence among three groups at 6, 12, 24, and 36 hours after completion of initial IVIG infusion. There were no differences in the incidence of coronary artery lesions during the study period (at week 2, month 1, month 3, and month 6 of illness), changes of laboratory data, total fever days, and length of stay. Group C patients had the lowest total dose of IVIG (mean: 1.2 vs 2.2 vs 2.1 g/kg; P < 0.001) and hospitalization expenses (mean: 8443.8 vs 10798.4 vs 11011.4 Chinese Yuan; P < 0.001) than other two groups. Conclusions: A single dose of 1g/kg IVIG is a low‐cost treatment with the same efficacy as 2 g/kg IVIG and can be an option for the initial therapy of KD patients.